Diagnóstico molecular de resistência antimicrobiana em cepas de Pseudomonas aeruginosa isoladas de pacientes em Unidade de Terapia Intensiva de um hospital universitário de Fortaleza, Ceará, Brasil - Maia, Marilia Silveira (2023)
Pseudomonas aeruginosa is an opportunistic pathogen of clinical relevance in intensive care units (ICUs), mainly due to its high resistance to several antimicrobials, which sometimes prevents effective treatment, leading to high morbidity and mortality of patients in critical situations. The aim of this study was to determine the main phenotypes and genotypes related to antimicrobial resistance in strains of P. aeruginosa isolated from patients admitted to the (ICU) of a teaching hospital in Fortaleza, Ceará, Brazil. This descriptive study analyzed strains isolated from these patients, collected from April 2019 to May 2021, in which phenotypic tests were performed for 15 drugs used in the antimicrobial susceptibility test (AST) used at the hospital in question. Using qPCR, 14 genes encoding β-lactamases and 13 genes encoding efflux pumps were evaluated to identify the genetic profile of resistance to antimicrobials of the isolates. During the period of this study, 258 Gram-negative bacteria resistant to at least one antimicrobial were isolated, of which 20.9% (54/258) were identified as P. aeruginosa, these isolates showed a phenotypic profile of resistance that varied from 100% to 28.3% among the drugs tested, except for colistin, ceftazidime/avibactam and ceftolozone/tazobactam, for which resistance was not verified. The genes related to β- lactamases most present in all isolates were the gene blaKPC 81.49% (44/54), blaCTXM-2 72.22% (39/54), blaCTXM-1 66.66% (36/ 54), blaCTXM-5 59.25% (32/54), blaSHV 40.74% (22/54), and finally, blaTEM and blaOXA-23 38.89% (21/54). There was an association between the presence of the genes: blaTEM and resistance to ceftazidime, cefepime, imipenem and meropenem (P=0.017; P=0.017; P=0.018 and P=0.034, respectively); blaOXA- 23 and ceftazidime and cefepime resistance (P=0.041) and blaOXA-51 and meropenem resistance (P=0.043). 100% positivity was observed for the genes that encode the MEX-AB, MEX-EF, MEX-GH, MEX-VW, MEX-XY efflux pumps, followed by 96.3% positivity for the MEX-CD gene, there was no statistical association between the phenotypic profile and the presence of efflux pumps. It is concluded that the strains of P. aeruginosa isolated in this study have an arsenal of genes encoding β-lactamases capable of inducing phenotypic patterns of resistance to several antimicrobials commonly used for these infections, making treatment difficult for the patient.